Advances in Economic Design 2003
DOI: 10.1007/978-3-662-05611-0_14
|View full text |Cite
|
Sign up to set email alerts
|

A Sequential Approach to the Characteristic Function and the Core in Games with Externalities

Abstract: Abstract. This paper proposes a formulation of coalitional payoff possibilities in games with externalities, based on the assumption that forming coalitions can exploit a "first mover advantage". We derive a characteristic function and show that when outside players play their best response noncooperatively, the core is nonempty in games with strategic complements. We apply this result to Cournot and Bertrand games and to public goods economies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
0
21
0
1
Order By: Relevance
“…Since it was already proved (e.g. Currarini and Marini, ) that in all games in which players actions are strategic complements λ ‐ and γ ‐core are non‐empty (see also Lardon, ) it does not come as a surprise that in a Cournot oligopoly game in which goods are complements (and actions strategic complements) the core is non‐empty if remaining firms form a sufficient number of coalitions in response to a deviation.…”
Section: Extensionsmentioning
confidence: 99%
“…Since it was already proved (e.g. Currarini and Marini, ) that in all games in which players actions are strategic complements λ ‐ and γ ‐core are non‐empty (see also Lardon, ) it does not come as a surprise that in a Cournot oligopoly game in which goods are complements (and actions strategic complements) the core is non‐empty if remaining firms form a sufficient number of coalitions in response to a deviation.…”
Section: Extensionsmentioning
confidence: 99%
“…The grand coalition inevitably falls apart and a stable but small coalition prevails. Extensions and modifications of the approach were proposed by Currarini/Marini [8] and Marini [9], but in this paper our focus is more on the incentives of single countries to enter or to leave a coalition and not on the characterization of cores of cooperative games. Other papers that come to relatively optimistic conclusions regarding the size of stable coalitions are concerned with issue linking, e.g., combining climate policies with trade or innovation policies.…”
Section: Introductionmentioning
confidence: 99%
“…A more general result for any number of firms is provided by Chander (2010). Currarini & Marini (2003) built a refinement of the γ-core by assuming that the deviant coalition acts as a Stackelberg leader in the product market. Zhao (1999) showed that the α and β cores of oligopolistic markets are non-empty.…”
Section: Introductionmentioning
confidence: 99%